(untitled) (International Journal of Engineering and Computer Science, 2017)
Cloud computing is an upcoming technology, which offers various services. The services include infrastructure, platform or software services. The service provided by the cloud is over the internet. In the Cloud, the services are available quickly. The cloud has high demand in the market. Most of the organisation or user prefers their storage as on cloud storage and which is located at the remote place. The user has no control over the cloud storage data. The cloud computing uses the resources like Memory, storage and processor, which are not physically present at the user’s location, rather they are located outside the premises and managed by a service provider. The user can access the resources via the Internet. The main focus of this paper is to check data integrity of file which is stored on remote cloud storage with less communication overhead.